The Influence of Milling Conditions on the Structure and Properties of Fe3O4 Nanoparticles for Biomedical Applications - Vladislav A. Mikheev; Timur R. Nizamov; Polina I. Nikolenko; Anna V. Ivanova; Alexander I. Novikov; Irina V. Dorofievich; Alexey S. Lileev; Maxim A. Abakumov; Igor V. Shchetinin (Crystals, 2024)
In this work, a new two-stage scalable method for the synthesis of magnetite nanoparticles for biomedical applications is proposed. The influence of the milling time, medium, and surfactants on the formation of the structure, magnetic, and functional properties of magnetite nanoparticles has been studied. Comprehensive investigation of the formation of the structure and properties of magnetite nanoparticles has been carried out using X-ray diffraction analysis, scanning and transmission electron microscopy, Mössbauer spectroscopy, measurements of magnetic properties, specific loss power (SLP), and cytotoxicity. It was shown that the milling medium of water with the addition of trisodium citrate is a harsher milling condition compared to octadecene-1 with the addition of oleic acid. Continuous milling for 50 h allowed to obtain a fraction of colloidally stable nanoparticles at the level of 80–90%. Harsher milling conditions led to the formation of a larger fraction of superparamagnetic particles, which reduced the coercivity and SLP. The maximum SLP value of 1140 W/g was reached by large particles, while nanoparticles had decreased SLP values of 100–190 W/g, which was completely determined by the coercivity dependence. Different synthesis conditions allowed obtaining particles with different cytotoxicity against PC-3 cells.